European Union News Themes in Romanian Radio Stations. Case Study: Europa FM and Radio Romania Actualitati - Antonia-Ioana Matei; Florica Iuhaş (EIRP Proceedings, 2013)
With Romania’s integration in the European Union, the media content related to the member states has acquired growing importance. The themes of journalism were enriched with new approaches towards national image in the European context and vice versa. At a first level, the study aims to conduct a quantitative analysis on the news topics broadcasted by Radio Romania Actualitati and Europa FM, for the duration of 32 days. The qualitative component focuses on the topics addressed in radio news in order to see what is the media content which reflects the image of the European Union. The findings show, beyond the numbers, that the editorial policy of the Romanian media is not concerned with the interests of the citizens - from the perspective of common themes - but rather with how can the EU, as a unified body, help member countries solve their problems.